Associations of the LPL S447X and Hind III Polymorphism with Type 2 Diabetes Mellitus Risk: A Meta-Analysis - Liu, Na; Sang, Yan; Chen, Shengzhi; Liu, Xiaoming (Hormone and Metabolic Research, 2020)
The present study was aimed to evaluate the association of lipoprotein lipase (LPL) gene (S447X and Hind III) polymorphisms and T2DM. Relevant studies were identified through systematic search PubMed, Cochrane Library, Embase, Wanfang, CNKI databases. A total of 22 studies (8 studies for LPL S447X and 14 studies for Hind III) were included. The results showed that the LPL S447X polymorphism was associated with the low risk of T2DM under dominant and allelic genetic models. Subgroup analysis by ethnicity showed that the LPL S447X polymorphism was associated with a decreased risk of T2DM in the Asian population (under dominant, heterozygous and allelic genetic models). In addition, we found that X allele carriers of S447X polymorphism is associated with low levels of TC, TG, and LDL. In subgroup analysis, Hind III polymorphism was associated with low risk of T2DM in Asian populations (under dominant, heterozygote, allele genetic models). Moreover, the carriers of H allele of Hind III have lower levels of TG, and higher levels of HDL-C. This meta-analysis demonstrated that 447X carriers and H allele in LPL gene associated with low risk of T2DM, which may due to in part to the change of serum level of TC, TG, LDL, and HDL.
Keywords: lipoprotein lipase; polymorphism; type 2 diabetes mellitus; S447X; Hind III